PENGARUH IKLM ORGANISASI TERHADAP LOYALITAS KERJA KARYAWAN PADA HOTEL BINTANG LIMA PEKANBARU - Era Anggriyani; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted at Bintang Lima hotel Pekanbaru. This Research aim to knowing the organization climate influence to the employee work loyality of Bintang Lima hotel Pekanbaru. Organization Climate as independent variable (X) And the employee work loyality as dependen variable (Y). This research takes the responder amount as much 26 people. In this research, data obtained by use the koesioner and interview with use the scale likert and for the nextto processed and analysed by trough the validity test, reliability test, statistican analysm wich is simple linear regression analysis, t test, correlation analysm and determination by using aid of Statistical Program for Social Sciences (SPSS) application. Result of this research wich is result of hypothesis t test, t calculate (6,782)> t table (2,064). It is means shown that organization climate is significantly influence to the employee work loyality. Where the value of coefficient of determination shown that intensive variable give the contribution to the employee work loyality variable at 65.7%  and the rest at34.3% influenced by others dissimilar variable which is not discussed in this research. Keywords :organization climate, employee work loyality.